The Value of Sarangani Bay as a waste sink for organic pollutants coming from livestock and poultry sectors - Arcamo, Sandra Mae V.
The study's main objective was to estimate the value of Sarangani Bay as waste sink for organic pollutants coming from the agricultural sector, specifically, the livestock and poultry sectors, focusing on quantifying the current level of water pollution in the bay and projecting or forecasting the level of water pollution discharges in the bay at year 2010. Secondary data on pollution discharges from livestock and poultry sectors were used to answer the objectives mentioned above. However, the data were based on physical estimation only, thus, the data were very hypothetical. The major pollutants involved are the biochemical oxygen demand (BOD), suspended solids (SS), and nitrate (NO3). The data involved the aggregate pollution discharges in General Santos City and Sarangani Province. Because of the increasing pattern of pollution discharge into the bay, water pollution was very prevalent. Even the forecasting result would show that the pollution in the bay would worsen as the years go by. Department of Environment and Natural Resources' standard would at least help minimize the pollution discharges since they would set a maximum allowable limit of effluent. DENR would also set a fine for sectors that exceeded the allowable limit in Sarangani Bay based on Pollution Adjudication Board (PAB) Resolution.